Clinical characteristics and perspectives of children and youths with type 1 diabetes attending Patan Hospital, Nepal - Paudel, Ujjawal; Paudyal, Buddhi Prasad; Kansakar, Prerana; Shakya, Mila (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Type 1 Diabetes Mellitus (DM1) has reportedly a high proportion of initial presentation as diabetic ketoacidosis, more in resource-poor settings. This study was designed to assess the demographics and clinical characteristics of DM1 patients as well as their perception of diabetes management in local scenario. Method: This is a cross-sectional study of data collected prospectively by a questionnaire survey among young patients with DM1 presenting to Medical and Paediatric Referral Clinics of Patan Hospital, Nepal during April 2016 to June 2016. Ethical approval was obtained. Demographics, and disease process- initial presentation of diabetic ketoacidosis, HBA1c target, and common problems were analyzed by SPSS using chi-square and Fisher exact tests, p<0.05 considered statistically significant. Result: Fifty-eight patients were enrolled in the study. Diabetic ketoacidosis was the initial presentation in 27(46.55%). A 15(27.78%) of surveyed patients had achieved age-specific goals of the HbA1c target. Financial issues and difficulty to come for regular follow-ups were the common problems in diabetes management. Conclusion: Diabetic ketoacidosis was a common initial presentation in nearly half of the DM1 patients. Three quarter of them didn’t have adequate control of the disease with age-specific goals of the HbA1c target.